2016
DOI: 10.1136/bcr-2016-216054
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural pathology of human liver in Rift Valley fever

Abstract: Rift Valley fever (RVF) is a zoonotic disease that primarily affects ruminant animals and can also cause fatal disease in humans. In the current report, we present the ultrastructural changes in the liver of a man aged 60 years who died from RVF in the Aseer Central Hospital, Abha, Saudi Arabia. The main hepatic changes by transmission electron microscopy included the presence of 95-115 nm electron-dense particles consistent with RVF virions, nuclear condensation, vacuolar degeneration, lipid droplet accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Acute hepatitis may complicate with prolonged blood coagulation times and may occur together with or precede fatal hemorrhages or neurologic complications. Autopsy studies and pathogenesis characterization in mouse model found evidence of liver necrosis with RVF viral antigens identified within hepatocytes and Küpffer cells, arguing for a direct virus-induced cellular necrosis [19,37,44,57,59,60]. A RVF case with a co-existing condition of cirrhosis after hepatitis B infection died as a result of gastrointestinal bleeding and hepatic encephalitis in Mayotte [28], and 4/31 (13%) severe cases described during the epidemic in Mauritania in 2015 had chronic hepatitis B [61], suggesting that patients with chronic hepatic ACUTE OR DELAYED ENCEPHALITIS day VISION DISORDERS day [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] disorders-mainly hepatitis B chronic infection-could be at higher risk of unfavorable outcome.…”
Section: Hepatic Manifestationsmentioning
confidence: 99%
“…Acute hepatitis may complicate with prolonged blood coagulation times and may occur together with or precede fatal hemorrhages or neurologic complications. Autopsy studies and pathogenesis characterization in mouse model found evidence of liver necrosis with RVF viral antigens identified within hepatocytes and Küpffer cells, arguing for a direct virus-induced cellular necrosis [19,37,44,57,59,60]. A RVF case with a co-existing condition of cirrhosis after hepatitis B infection died as a result of gastrointestinal bleeding and hepatic encephalitis in Mayotte [28], and 4/31 (13%) severe cases described during the epidemic in Mauritania in 2015 had chronic hepatitis B [61], suggesting that patients with chronic hepatic ACUTE OR DELAYED ENCEPHALITIS day VISION DISORDERS day [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] disorders-mainly hepatitis B chronic infection-could be at higher risk of unfavorable outcome.…”
Section: Hepatic Manifestationsmentioning
confidence: 99%